TRANSFORMATIONAL LEADERSHIP AS A DETERMINING FACTOR FOR TEACHER MOTIVATION IN THE SECONDARY SCHOOL ENVIRONMENT - Yuliantina, Irma; Santoso, Priyo; Iswanto, Wiwit (Jurnal Multidisipliner Bharasa, 2024)
This study aims to analyze the role of transformational leadership as a determining factor for teachers' work motivation in the secondary school environment. Transformational leadership was chosen because of its characteristics that are able to inspire, motivate, and empower teachers to achieve higher performance. This study uses a quantitative approach with a survey method involving 150 teachers from various secondary schools in Indonesia. The research instrument used was a questionnaire consisting of items that measured the dimensions of transformational leadership and the level of teacher motivation. The results of the study showed that there was a significant positive relationship between transformational leadership and teacher motivation. In particular, the dimensions of leader charisma, intellectual stimulation, and individual consideration contribute significantly to the improvement of teachers' work motivation. These findings indicate that school principals who apply transformational leadership styles can increase teacher motivation, which in turn has a positive impact on the learning process and student learning outcomes. This research provides practical implications for the development of education policies, especially in the selection and training of school principals who are able to implement transformational leadership styles. Thus, it is hoped that a conducive school environment can be created for improving the quality of education in Indonesia. The study also identifies areas for further research to deepen understanding of leadership dynamics and motivation in the context of education.